Intervensi Manajemen Sumberdaya Manusia dan Dampaknya terhadap Kesiapan Sivitas Akademika untuk Berubah - Azzuhri, Misbahuddin (Jurnal Aplikasi Manajemen, 2016)
Creating change readiness may be one of the key factors in determining whether a given change intervention will ultimately be successful or not. For higher education institution to assist academic society in being motivated and prepared for change, it is essential that leaders, lecturers, employees, and also students understand factors that may influence readiness for change. The purpose of this research study was to investigate the impact of human resource management intervention consisting of goal setting, performance appraisal, and reward system toward readiness for change. The data was collected through a survey using self-reported questionnaire and accidental sampling. Survey responses collected from a sample of 100 university students in three departments in higher education organization which are continuing the process of transformation. The findings indicate that there are significant effect of performance appraisal on readiness for change. This study were also found significant effect of reward system toward readiness for change. However, the results indicate that goal setting has no impact on readiness for change. Additionally, the implications and applications of these findings are discussed.Â